(untitled) (Malaysian Journal of Civil Engineering, 2020)
Identify and select a suitable ground motion intensity measure (IMs) parameters associated with the structural response to specific levels of damages or collapse in structures are very important in the seismic response of structural analyses. This paper investigated the correlation between 25 intensity measure (IMs) parameters of earthquakes and the structural response parameters of 3-, 6- and 12-story moment resisting steel frames (MRSFs). Nonlinear time history analyses are performed for these frames under near- and far-source ground motion records. The maximum story drift ratio (MSDR), the roof drift ratio (RDR), and the maximum base shear force (SF) are chosen as the structural response parameters. The Pearson correlation coefficient with the regression analyses is utilized to display the correlation between the structural response parameter and the ground motion IMs parameters. The results reveal that MSDR appears to be a suitable engineering demand parameter to correlate with most of the ground motion IMs parameters compared to both the RDR and the SF parameters. Also, Max. Incremental velocity (MIV) parameter is considered as the highest correlated IMs parameters with MSDR in both near- and far-source earthquakes.